2021
DOI: 10.1021/acs.jmedchem.1c00759
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of First-in-Class Peptidomimetic Neurolysin Activators Possessing Enhanced Brain Penetration and Stability

Abstract: Peptidase neurolysin (Nln) is an enzyme that functions to cleave various neuropeptides. Upregulation of Nln after stroke has identified the enzyme as a critical endogenous cerebroprotective mechanism and validated target for the treatment of ischemic stroke. Overexpression of Nln in a mouse model of stroke results in dramatic improvement of stroke outcomes, while pharmacological inhibition aggravates them. Activation of Nln has therefore emerged as an intriguing target for drug discovery efforts for ischemic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The reaction was stopped by addition of 1 µl of 1.0 N LCMS grade HCl and storage at −80°C freezer. Quantification of Ang II and its hydrolysis product Ang-(1-7) was carried out by LC-MS/MS using a SCIEX Triple Quad™ 5500+ LC-MS/MS System following a protocol modified from our recent studies (Jayaraman et al, 2021;Rahman et al, 2021). In brief, 2 μl of sample was injected onto a 50 × 2.1 mm Kinetex EVO C18 column (Phenomenex).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction was stopped by addition of 1 µl of 1.0 N LCMS grade HCl and storage at −80°C freezer. Quantification of Ang II and its hydrolysis product Ang-(1-7) was carried out by LC-MS/MS using a SCIEX Triple Quad™ 5500+ LC-MS/MS System following a protocol modified from our recent studies (Jayaraman et al, 2021;Rahman et al, 2021). In brief, 2 μl of sample was injected onto a 50 × 2.1 mm Kinetex EVO C18 column (Phenomenex).…”
Section: Methodsmentioning
confidence: 99%
“…203 Whilst the inhibition of Nln is a mechanism that has been exploited for the design of therapeutic agents to target acute myeloid leukemia, 204 it has recently been identified that the activation of Nln may provide a route to identify therapeutics for the treatment of neurodegenerative diseases, including ischemic stroke. 203,205,206 Activator NSC 374121(24) (Fig. 19) was identified as a hit from a virtual screen with an A 50 value of 89.7 μM.…”
Section: Neurolysinmentioning
confidence: 99%
“…[207][208][209][210] In vitro metabolic stability studies reported that each of the three analogues had significantly increased half-lives in mouse plasma compared to the original hit, which reported a half-life of 34.19 minutes, in comparison to compounds 25 and 26, which presented the best half-lives of >1000 minutes. 205 The permeabilities of each of the compounds were obtained within the MDR1-MDCA cell line, in which 26 and 27 presented the best permeability. Compound 26 presented a permeability greater than 15 × 10 −6 cm s −1 , while 27 presented a permeability of 20 × 10 −6 cm s −1 in the basolateral to apical direction, suggesting a higher efflux ratio, allowing for increased drug concentrations within the brain.…”
Section: Neurolysinmentioning
confidence: 99%
“…13 The development of small-molecule enzyme activator compounds is rapidly becoming a viable therapeutic discovery strategy for many diseases. 14,15 In our efforts to identify Nln activator compounds for stroke, we previously disclosed a peptidomimetic scaffold represented by Nln-10c and Nln-11a, 16 optimized from a dipeptide hit (HY) obtained from a high-throughput screen (Figure 1). 17 Both compounds possessed "drug-like" pharmacokinetic parameters, including brain penetration.…”
mentioning
confidence: 99%
“…Selected synthetic intermediates en route to the imidazole bioisostere were subjected to Nln activation determination. Previously obtained 4-chloro­phenyl­ethyl derivative 14 ( A 50 = 25 μM, A max = 404.4%) was approximately 2-fold less active than the corresponding fluoro-substituted derivative 15 , an observation agreeing with the previously observed preference for electron-withdrawing groups on the terminal phenyl ring in these structures . Introduction of a ketone α to the phenyl ring to afford 11b lowered A 50 (33.7 μM) and substantially reduced A max (130%) compared with the saturated parent 14 .…”
mentioning
confidence: 99%